Analysis of Supervised algorithm for Voice Query Classification (International Journal of Engineering and Computer Science, 2014)
Categorization of voice queries is useful for the finding the intent of the user.  By finding intent it is easy to monitor that user.  By performing classification search engine can find the class of the query. By using that class it becomes easy for the search engines to retrieve the results which are already classified in that class. This classification is useful for the targeted advertisement depending on search queries. For that classification two algorithms are used and analyzed. This analysis is based on the different parameters.